1996
DOI: 10.1136/gut.39.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Prospective controlled trial of duplicated (J) versus quadruplicated (W) pelvic ileal reservoirs in restorative proctocolectomy for ulcerative colitis.

Abstract: Conclusions-These findings provide support for the use of a relatively small (30 cm), duplicated (J) ileal reservoir, which is simple to construct with linear stapling instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…However, another prospective controlled trial comparing short (30 cm ileum) or long (40 cm ileum) duplicated (J) versus short (30 cm ileum) or long (40 cm ileum) quadruplicated (W) IPAA showed that the bowel frequency in smaller J reservoirs did not differ significantly from bowel frequency in the bigger W reservoirs. Patients with the large W40, however, had the lowest frequency of the four groups [21]. This is in line with our results, as the bowel frequency after the W reservoir was about the same as after the J reservoir.…”
Section: Discussionsupporting
confidence: 91%
“…However, another prospective controlled trial comparing short (30 cm ileum) or long (40 cm ileum) duplicated (J) versus short (30 cm ileum) or long (40 cm ileum) quadruplicated (W) IPAA showed that the bowel frequency in smaller J reservoirs did not differ significantly from bowel frequency in the bigger W reservoirs. Patients with the large W40, however, had the lowest frequency of the four groups [21]. This is in line with our results, as the bowel frequency after the W reservoir was about the same as after the J reservoir.…”
Section: Discussionsupporting
confidence: 91%
“…However, there was no significant difference in bowel frequency between the J-and W-pouches or between the 30-cm and 40-cm reservoirs. Similarly, Johnston et al 6 concluded, on the basis of a randomized controlled trial comparing J-and W-pouches, that the J-pouch was preferable because of the simplicity of its construction. The main drawback of these studies is the small patient numbers and the absence of long-term results on pouch function.…”
mentioning
confidence: 96%
“…But an ileal pouch with an anal anastomosis of one configuration or another remains the preferred means of improving quality of life for these patients. 3 As evidenced in the literature, this surgery is also useful for patients with conditions other than ulcerative colitis, particularly those properly selected patients who have colorectal cancer, familial adenomatous polyposis, or Crohn's disease. Approximately one sixth of patients undergoing IPAA at our facility did so for indications other than ulcerative colitis.…”
Section: Discussionmentioning
confidence: 97%